IMPROVING DISSEMINATION OF WEATHER INFORMATION SERVICES THROUGH LOCAL CABLE TV NETWORKS IN NAIRA - Kasmanto, Rony; Kainama, Carisz; Darmawan; Haryoko, Urip (Jurnal Widya Climago, 2023)
This change action plan is an effort to increase the percentage of the Naira community receiving weather information provided by the station. receiving weather information provided by Class III Bandaneira Meteorological Station - Central Maluku. The purpose of this change action plan is to improve the dissemination of weather information services at Bandaneira Meteorological Station through the Cable TV network, and followed by socialisation to the community to facilitate the community in accessing weather information. The change action "Improving the Dissemination of Weather Information Services through the Local Cable TV Network" has helped Bandaneira Meteorological Station in improving performance in terms of public services to the community. Through socialisation conducted by an effective team in introducing Cable TV media as an alternative means of dissemination in addition to the social media already owned by Bandaneira Meteorological Station, it has made it easier for people who have limited internet access to access or obtain weather information services so that they can help in supporting their daily activities.